Household Wealth and Women’s Health: Evidence from India - Shengjie Zhu (Journal of World Economy, 2023)
The relationship between socioeconomic status and health, especially the link between income and health, has been extensively studied, but wealth still needs to be researched. This report uses India’s female BMI index from 2019 to 2021 as a health indicator to research the relationship between household wealth and health. The study results from show that household wealth positively correlates with BMI unhealthy indicators formed by underweight, obese, and overweight, which means that the possibility of unhealthy conditions will also increase with wealth. This relationship is because the rise of wealth reduces underweight but increases the incidence of overweight and obesity. This suggests that in India, the problem of obesity may outweigh the negative effects of malnutrition. In addition, increasing age and improving educational background can effectively reduce the probability of unhealthy occurrences. The feedback of these results can help the authorities have a more multi-dimensional understanding of women’s health and provide a new perspective for them to formulate more reasonable policies and improve women’s medical welfare policies.